SUSTAINING CULINARY MSMEs THROUGH ADAPTIVE STRATEGIES IN ECONOMIC CRISIS - Yunita Mustika (GREET, 2024)
This study examines how culinary micro, small, and medium enterprises (MSMEs) sustain operations during economic crises, with a particular focus on the COVID-19 pandemic. The research is driven by the urgent need to understand adaptive strategies that enable these businesses to remain viable amid severe disruptions. A qualitative approach was employed, integrating in-depth interviews, focus groups, and direct observations with culinary MSME owners and employees. This methodology captured the strategic, operational, and human dimensions of adaptation that quantitative data alone could not fully reveal. The findings indicate that digital transformation, product diversification, and community engagement were the most critical survival strategies. Businesses that rapidly embraced online platforms for sales and marketing experienced up to a 30% increase in revenue compared to non-adopters. Community partnerships—especially with local farms and suppliers—ensured stable supply chains and reinforced resilience. Notably, case studies highlight that operational agility, emotional resilience, and active customer engagement through digital channels were decisive factors in maintaining revenue streams and fostering loyalty. The study also underscores the importance of government support in providing financial assistance, training programs, and regulatory flexibility. These results contribute to the broader discourse on sustainable business practices by demonstrating that resilience is not solely dependent on financial resources but also on innovation, adaptability, and strong community ties. Policymakers, entrepreneurs, and stakeholders can apply these insights to design strategies that strengthen the sector’s long-term viability, cultural significance, and economic contribution.